Determinants of Customer Experience and Satisfaction in Online Food Delivery Services in Malaysia - Daisy Mui Hung Kee; Seng Xu Jong; Jeremy Jin Wei Wong; Keerthi A/P Kumaraguru; Yu Xuan Jia (AIBPM Publisher, 2026)
The rapid expansion of online food delivery (OFD) platforms has reshaped consumer food consumption patterns, particularly in emerging digital markets such as Malaysia. As GrabFood continues to dominate the Malaysian OFD sector, understanding the determinants of customer satisfaction has become increasingly important. This study aims to examine the effects of perceived usefulness, perceived ease of use, perceived trust, perceived risk, and perceived convenience on customer satisfaction, with customer experience serving as an intermediary variable. A quantitative, cross-sectional research design was employed using an online questionnaire administered to 200 active GrabFood users in Malaysia. Data were analyzed using regression analysis to test the proposed hypotheses. The results indicate that perceived convenience has the strongest positive effect on both customer experience (? = 0.421, p 0.001) and customer satisfaction (? = 0.141, p 0.05). Perceived ease of use (? = 0.334, p 0.001) and perceived trust (? = 0.255, p 0.001) significantly influence customer experience, while customer experience itself significantly predicts customer satisfaction (? = 0.405, p 0.001). In contrast, perceived usefulness and perceived risk show no significant direct effects. These findings suggest that experiential and convenience-driven factors outweigh functional considerations in shaping customer satisfaction within Malaysia’s mature OFD market.